PEMANFAATAN BUNGA SEPATU SEBAGAI BAHAN PEMBUATAN KERTAS INDIKATOR pH UNTUK MENDUKUNG KEGIATAN PEMBELAJARAN PADA PRAKTIKUM ASAM BASA DI SMA NEGERI 1 JATINOM KABUPATEN KLATEN - Siti Fatimah; Nadia Ika Rachma; Sugesti Retno Utami (ABDIMAS UNWAHAS, 2018)
education system in the educational unit experienced many problems, both in terms of distribution of education, learning opportunities, and lack of means of education and lack of learning resources available and use was to assist the implementation of the learning process. One alternative to the education problem solving through the application of learning technologies is to empower the learning resources that are designed and used and managed for the purpose education, such as utilizing the natural resources around. Utilization of natural resources can be applied in learning about chemistry, such as for example in the materials acid-base titration using natural indicators. An example is the use of extracts of hibiscus. The use of extracts of hibiscus in learning chemistry is an indicator of acid-base titration. During this time the use of acid-base indicators include the litmus paper and an indiator form of a solution such as methyl orange and phenolftalein. This synthetic indicator can be an alternative support or medium of learning in the selection of environmentally friendly indicator. Shoe flower extract is then made into paper form pH so that it can be used as an acid-base indicatorKeywords:extract, hibiscus, indicators, acid-base